Bipolar host materials based on diphenylphosphine oxide and carbazole derivatives with high triplet energy: Synthesis, characterization and photoelectronic performance in PhOLEDs. (June 2018) - Yang, Tingting; Xu, Huixia; Wang, Kexiang; Tao, Peng; Wang, Fang; Zhao, Bo; Wang, Hua; Xu, Bingshe
Abstract: Three novel host materials based on carbazole (Cz) and diphenylphosphine oxide (DPPO) by the different linkages method were designed and synthesized, named (3'-(9H-carbazol-9-yl)-[1, 1′-biphenyl]-4-yl)diphenylphosphine oxide (CzPhPO ), (4-(9-phenyl-9H-carbazol-2-yl)phenyl) diphenylphosphine oxide (2PhCzPO ) and (4-(9-phenyl-9H-carbazol-3-yl)phenyl) diphenylphosphine oxide (3PhCzPO ). Their thermal stability, photophysical and electrochemical properties were investigated and optimized by tuning the linking modes between electron acceptor DPPO and electron donor Cz. The triplet energy ( E T ) ofCzPhPO, 2PhCzPO and3PhCzPO were 2.79, 2.55 and 2.70 eV, respectively. As a result, equipped with the bipolar transport properties, the blue phosphorescent organic light-emitting device (PhOLED) fabricated withCzPhPO doped with iridium(III) bis[(4, 6-difluorophenyl)-pyridinato-N, C 2' ]picolinate (FIrpic) had achieved a low turn-on voltage of 2.9 V, a maximum power efficiency of 33.7 lm/W, corresponding a maximum external quantum efficiency (EQE) of 15.8% as well as a low efficiency roll-off. EmployingCzPhPO, 2PhCzPO and3PhCzPO as hosts, green PhOLEDs with tris(2-phenylpyridine)iridium (Ir(ppy)3 ) as an emitter displayed EQEs of 19.7, 18.7 and 17.8%, respectively. Graphical abstract: Abstract : Three bipolar host materials were synthesized by using diphenylphosphine oxide as acceptor and carbazole units as donor. The triplet energies ofCzPhPO and3PhCzPO reach to 2.79 and 2.70 eV. The blueCzPhPO -based PhOLEDs by using FIrpic as emitter exhibits high performance with EQE max of 15.8%.